Gut Microbiota on the Incidence of Hypertension in Elderly Aged 60-89 Years : Scoping Review - Untari; Setia Putri , Lintang; Raudatul Zannah , Nurul; Nur Indah , Citra; Katyana Anindita, Gina (UNIVERSITAS NGUDI WALUYO, 2026)
Hypertension is a growing global health problem. Identification of the causes of hypertension is highly variable and challenging, but in reality, it is multifactorial, both internal and external, including genetic, environmental, hormonal, and inflammatory factors. Hypertensive patients have decreased gut microbiota diversity, which is strongly correlated with the presence of gram-negative bacteria, such as Klebsiella, Streptococcus, Parabacteria, Desulfovibrio, Prevotella. This article aims to review the results of previous research related to the influence of gut microbiota on the incidence of hypertension in the elderly, as well as the mechanisms that link gut microbiota to the occurrence of hypertension in the elderly. The method used is a scoping review with the PICOS approach (Population, Intervention, Comparison, Outcome, Study Design) in compiling questions as a reference to identify keyword concepts that are appropriate to the objectives and questions reviewed and to determine inclusion and exclusion criteria. The elderly tend to have more Enterobacteriaceae and Oscillospira associated with inflammation, whereas younger people have more Bifidobacteria and SCFA-producing bacteria. The elderly with hypertension exhibit significant differences in gut microbiota composition. Longer-lived individuals have a higher proportion of short-chain fatty acid (SCFA)-producing bacteria such as Bacteroides, Faecalibacterium, and Alistipes, which play a role in stabilizing blood pressure through acetate production. The gut microbiota is a key component in the pathophysiology of hypertension in the elderly, with dysbiosis contributing to inflammation, metabolic disturbances, and decreased therapeutic efficacy. The reviewed studies suggest that SCFA-producing microbiota have protective effects and may be a potential target in hypertension management strategies.